Семантичні аспекти термінів екомаркетингу сучасної англійської мови - Кушнерук, Світлана Миколаївна; Kushneruk, S. M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто різні підходи до вивчення терміна як частини лексичної системи літературної мови, проаналізовано семантичні аспекти англійських термінів на прикладі термінів екомаркетингу та сучасний стан дослідження цієї терміносистеми, окреслено поняття екомаркетингу, терміна та терміносистеми екомарке¬тингу, що сприятиме подальшому опрацюванню широкого кола питань, пов’язаних із дослідженням термінів екомаркетингу сучасної англійської мови. This article is an attempt to reveal the problem of determining the semantic aspects of English eco marketing terminology. In recent years linguists pay a lot of attention to the study of terminological systems that arise at the intersection of science. Eco marketing terminology belongs to such terminological systems. Despite different approaches to the study of terms, most linguists agree that the terms are not isolated units. They have the same language functions as common words. Also linguists identified a number of requirements to the terms. Eco marketing terminology is one of the most dynamic terminological systems. It has the examples of synonyms, antonyms and polysemy. The study of eco marketing terminology provides an opportunity to improve and streamline this terminology and helps the formation of the corresponding Ukrainian terminological system.
Semantic Aspects of Modern English Eco Marketing Terms
Keywords: терміносистема; terminological system; термін; term; екомаркетинг; eco marketing